2017
DOI: 10.1073/pnas.1701400114
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of surface diffusion and relaxation dynamics of molecular glasses

Abstract: Tobacco mosaic virus is used as a probe to measure surface diffusion of ultrathin films of ,-Bis(3-methylphenyl)-,-diphenylbenzidine (TPD) (12 nm [Formula: see text] 53 nm, where [Formula: see text] is the film thickness) at various temperatures below the glass transition temperature, [Formula: see text], of all films. As the film thickness is decreased, [Formula: see text] decreases rapidly and the average film dynamics are enhanced by 6-14 orders of magnitude. We show that the surface diffusion is invariant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 37 publications
5
74
1
Order By: Relevance
“…However, the most striking feature from the Zhang and Fakhraai investigation (8) was obtained when the T g measured by ellipsometry as a function of film thickness is compared with D s (8). In agreement with previous measurements, a reduction in the T g with decreasing film thickness was observed for TPD; the T g of a 12-nm film was reduced by ∼15 K. Thus, the state of affairs that emerged from this study was the following: despite a reduction in T g and molecular relaxation (17), D s remained invariant under the same conditions (Fig.…”
Section: A1mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the most striking feature from the Zhang and Fakhraai investigation (8) was obtained when the T g measured by ellipsometry as a function of film thickness is compared with D s (8). In agreement with previous measurements, a reduction in the T g with decreasing film thickness was observed for TPD; the T g of a 12-nm film was reduced by ∼15 K. Thus, the state of affairs that emerged from this study was the following: despite a reduction in T g and molecular relaxation (17), D s remained invariant under the same conditions (Fig.…”
Section: A1mentioning
confidence: 99%
“…However, exactly how this enhanced mobile layer is correlated to the measured changes in T g and the corresponding underlying molecular dynamics has remained an intriguing, and a far-from-understood question (6,7). Reporting in PNAS, Zhang and Fakhraai found that the surface diffusivity of ultrathin films of a molecular glass former was enhanced compared with bulk and independent of film thickness, despite a concurrent dramatic reduction in the T g and enhancement in the relaxation dynamics within confinement (8).…”
Section: A1mentioning
confidence: 99%
See 2 more Smart Citations
“…Several theoretical models were proposed to address this huge enhancement of surface mobility of small molecule OGs [5][6][7] and metallic glass. 8 Recently Fakhraai and coworkers [9][10][11] have investigated the effect of variations in bulk dynamics on the surface diffusion of the molecular glass, N,N 0 -bis(3-methylphenyl)-N,N 0 -diphenylbenzidine (TPD) with its ordinary T g = 330 K. Using the tobacco mosaic virus as a probe particle, they measured D S (T) on glasses of the same composition but with a large difference in bulk relaxation dynamics and in the glass transition temperature. The glasses of TPD include the ordinary glass (OG) obtained by liquid quenching, annealed glass after physical aging at 0.9T g for a week, ultrastable glass (SG) fabricated by physical vapor deposition at various substrate temperatures, and 12 to 30 nm thin films.…”
Section: Introductionmentioning
confidence: 99%